Smoking‐related idiopathic interstitial pneumonia: A review. Issue 1 (2nd July 2015) - Margaritopoulos, George A.; Harari, Sergio; Caminati, Antonella; Antoniou, Katerina M.
Abstract: For many years, cigarette smoking has been considered as the leading cause of chronic obstructive pulmonary disease and lung cancer. Recently, however, it has also been associated with the development of diffuse interstitial lung diseases. In the latest classification of the major idiopathic interstitial pneumonias (IIP), the term smoking‐related IIP has been introduced, including two entities, namely desquamative interstitial pneumonia (DIP) and respiratory bronchiolitis‐interstitial lung disease (RB‐ILD). Other entities in which smoking has a definite or suggested role include pulmonary Langerhan's cell histiocytosis, smoking‐related interstitial fibrosis, combined pulmonary fibrosis and emphysema syndrome and idiopathic pulmonary fibrosis. In this review, we will focus on the mechanisms of smoking‐related lung damage and on the clinical aspects of these disorders with the exception of idiopathic pulmonary fibrosis, which will be reviewed elsewhere in this review series. Abstract : Multiple small, irregularly shaped, cysts of varying sizes are present with thin walls in the upper lung lobes of patients with pulmonary Langerhans cell histiocytosis (PLCH; Left). A high magnification micrograph of Langerhans cell histiocytosis shows that Langerhans type histiocytes are CD1a dendritic cells in the lung with a reniform (or kidney–shaped) nucleus (Right).